Desain Kawasan Wisata di Taman Nasional Wasur - Muchlis Alahudin; Anton Topan; Sugeng Pujo Raharjo (Musamus Journal of Architecture, 2020)
Merauke is a district that is located in the southernmost part of Papua province and the most eastern part of the territory of the Republic of Indonesia. The wealth of tourism assets which is a combination of natural scenery and cultural uniqueness is also abundant. So far, the tourist attraction in Wasur National Park is still not sufficient to make it a tourist destination that can attract tourists. So that in this area, facilities that can help tourists with information, accommodation and transportation services are needed, including lodging, restaurants, travel agency, recreational park, souvenir shop, and so on. The method used is the descriptive method (to describe), namely: a method for looking for elements, characteristics and characteristics or phenomena. This method begins by collecting data and analyzing data using field survey techniques, comparative studies, literature studies, interviews / questionnaires, site analysis and building analysis. Where the data and analysis obtained can be used as a reference in the design of the tourist area in Wasur National Park, Merauke Regency. The result of this research is to get a container (Tourist Area in Wasur National Park) which is comfortable and can create harmony between humans and nature.